Effectiveness of 4 doses of COVID-19 vaccine in patients on maintenance hemodialysis in 5th wave of COVID-19 infection in Myanmar: Do we need 5 doses? - Pyar, Khin Phyu; Myint, Moe Zaw; Hla, Sai Aik; Hlaing, Soe Win; Aung, Aung; Yein Lwin, Kyaw Thu; Maung, Lay Maung; Hein, Ye Min; Aung, Lynn Htet; Thant, Myo Min; Maung, Myo Maung; Zaw, Moe Htun; et al. (International Journal of Medical Science and Clinical Research Studies, 2022)
Background: Patients on maintenance hemodialysis (MHD) are at high risk of contracting SARS-CoV-2 and developing severe COVID-19 infection because they have low innate immunity as well as poor antibody response to COVID-19 vaccine. This study aimed to assess the effectiveness of 4 doses of COVID-19 vaccine in preventing 5th wave of COVID-19 infections in patients on maintenance hemodialysis in Myanmar. Methods: A hospital-based descriptive study was conducted in July 2022 to November 2022 among patients on MHD who received COVID-19 vaccine 4 doses; last dose was 2 weeks ago. Data were collected by using standardized forms and analysis was done. Results: A total of 61 patients on maintenance hemodialysis ( MHD) who had 4 doses of COVID-19 vaccination more than 2 weeks were included. Nasopharyngeal swab PCR was taken twice a week to all patients (if they did not have symptoms) and it was repeated if they had symptoms suggestive of COVID-19 infection or they had history of contact with patients having COVID-19 infection. Their signs and symptoms were analyzed; chest radiograph and blood tests were taken if indicated. Then, the severity of COVID-19 infection was determined according to WHO criteria and they were given treatment according to hospital guideline. They were followed up till 28 days. The base line characteristics were as follows: mean age was 51.15 ± 12.85 years; male to female ratio was 4:6; mean BMI was 19.93 ± 2.83 kg/m2; 16.4%(10/61) had diabetic nephropathy; 9.8%(6/61) had cerebrovascular accident; 24.6%(15/61) had coronary heart disease; and one fifth of them were current smokers. Sixty six percent had past history of COVID-19 infection; duration from last infection was 404 days. Thirty three percent of cases had shortest duration of hemodialysis (6 months) and 23% were over 3 years. Mean duration from last vaccination was 39 days. Thirty six percent (22/61) had confirmed COVID-19 infection and 64% (39/61) of them were not infected till the end of 5th wave. All infected cases were mild form according to WHO criteria; none of them required oxygen therapy. One case having multiple comorbidities (lymphoma, coronary heart disease, hypertension and malignant cachexia) had sudden death due to pulmonary embolism. Conclusions: The protection rate of four doses of COVID-19 vaccine in patients on MHD was not good as 36% of them were infected in the 5th wave of epidemic in Myanmar. However, all the infected cases were mild form and they did not need oxygen therapy showing that booster vaccination prevented morbidity and mortality. Therefore, the protection rate of four doses of COVID-19 vaccine in patients on MHD was nearly 65%; it reduced the severe form of infection and death. Fifth dose of COVID-19 vaccine is necessary along with personnel protective measures.